Rhetorical argumentation, de C.Tindale - Molina, Jorge Alberto (Princípios: Revista de Filosofia (UFRN), 2010)
Resenha do livro de Tindale, C. Rhetorical argumentation. Principles of Theory and Practice. Thousand Oaks: SAGE Publications, 2004.